2010
DOI: 10.1371/journal.pone.0011629
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Iron Uptake Is Responsible for Differential Sensitivity to V-ATPase Inhibitors in Several Cancer Cell Lines

Abstract: Many cell lines derived from tumors as well as transformed cell lines are far more sensitive to V-ATPase inhibitors than normal counterparts. The molecular mechanisms underlying these differences in sensitivity are not known. Using global gene expression data, we show that the most sensitive responses to HeLa cells to low doses of V-ATPase inhibitors involve genes responsive to decreasing intracellular iron or decreasing cholesterol and that sensitivity to iron uptake is an important determinant of V-ATPase se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…To determine whether the increased LC3-II:LC3-I ratio was due to an overall increase in autophagy or a block in autophagosome turnover, we treated the cells with bafilomycin A 1 (Baf) to inhibit autophagic flux. 26 Since Baf can potentially disrupt the endocytic trafficking of TF, we also used chloroquine 29 and found that the LC3-II:LC3-I ratio was higher in cells treated with iron and either Baf or chloroquine than in cells treated with Baf or chloroquine alone (Fig. 1B and C).…”
Section: Iron Treatment Induces Ferritinophagymentioning
confidence: 99%
“…To determine whether the increased LC3-II:LC3-I ratio was due to an overall increase in autophagy or a block in autophagosome turnover, we treated the cells with bafilomycin A 1 (Baf) to inhibit autophagic flux. 26 Since Baf can potentially disrupt the endocytic trafficking of TF, we also used chloroquine 29 and found that the LC3-II:LC3-I ratio was higher in cells treated with iron and either Baf or chloroquine than in cells treated with Baf or chloroquine alone (Fig. 1B and C).…”
Section: Iron Treatment Induces Ferritinophagymentioning
confidence: 99%
“…Using global gene expression data Straud et al found that the increased sensitivity to V-ATPase inhibitors observed in cancer cells was correlated to their greater dependence on iron uptake, presumably to compensate their ROS production [113]. Wnt/ -catenin pathway is an important tumourigenic signal in many cancer cell types, e.g.…”
Section: Cell Biology Of V-atpase Inhibitionmentioning
confidence: 99%
“…Alongside its contribution to neurodegeneration, increased intracellular iron and the resultant OS can also potentiate tumor development (10,12,23,24,29,38). Ironically, after contributing to the insult that initiated tumor development, increased cellular iron is then a critical element required for the continued growth of tumors in a number of different cancer types (10,12,23,24,38).…”
Section: G558 Iron Loading and Oxidative Stress In Thementioning
confidence: 99%
“…Ironically, after contributing to the insult that initiated tumor development, increased cellular iron is then a critical element required for the continued growth of tumors in a number of different cancer types (10,12,23,24,38). A-T patients are predisposed to a variety of cancers, with one of the most significant clinical features of A-T disease being the incidence of lymphoid tumors that develop in Ïł30% of A-T patients (for review, see Ref.…”
Section: G558 Iron Loading and Oxidative Stress In Thementioning
confidence: 99%